EFFICIENCY OF TRANSPORTATION AND INDUSTRIAL CLUSTERING - A. Kurbatova; P. Ovchinnikov (Вестник университета)
The article considers approaches to evaluation of clustering of the economy and its impact on the efficiency of transportation (industrial) complex. It formulates an approach to the evaluation of the effectiveness on the basis of selected critical elements of the cluster. Authors propose definition of competitiveness as a dynamic component of effectiveness.